Claude Lévi-Strauss, Pierre Monbeig et Roger Brunet - Hervé Théry (EchoGéo)
Claude Lévi-Strauss travelled with Pierre Monbeig in the pioneer fringes of São Paulo state: evidences of those trips can be found in his work, in the words he uses but also in observations announcing future researches in indigenous societies, located further inland. Amongst those, the quest for underlying social and spatial structures, expressed in graphical form, seems to be forerunners of the work of another geographer, Roger Brunet.